Identification of Escherichia coli isolated from flies (Insecta: Diptera) that inhabit the environment of dairy farms harboring extraintestinal virulence markers - Motta, Rodrigo G; Motta, Lorrayne S. A. M [UNESP]; Bertolini, Amanda B [UNESP]; Prado, Aline M; Thyssen, Patricia J; Hernandes, Rodrigo T [UNESP]; Orsi, Henrique [UNESP]; Rall, Vera L. M [UNESP]; Gouvea, Fábio L. R [UNESP]; Guerra, Simony T [UNESP]; Guimarães, Felipe F [UNESP]; Joaquim, Sâmea F [UNESP]; et al. (Oxford University Press (OUP), 2023)
Aims: We investigate extraintestinal pathogenic genes (ExPEC) related to virulence of Escherichia coli in flies from the dairy environment. Methods and Results: We collected 217 flies from nine dairy farms, which were submitted to microbiological culture. Fifty-one E. coli were identified using mass spectrometry. Eleven dipteran families were identified, with a predominance of Muscidae, and a minor frequency of Tachinidae, Drosophilidae, Sphaeroceridae, Ulidiidae, Syrphidae, Chloropidae, Calliphoridae, Sarcophagidae, and Piophilidae. A panel of 16 virulence-encoding genes related to ExPEC infections were investigated, which revealed predominance of serum resistance (traT, 31/51 = 60.8%; ompT, 29/51 = 56.9%), iron uptake (irp2, 17/51 = 33.3%, iucD 11/51 = 21.6%), and adhesins (papC, 6/51 = 11.8%; papA, 5/51 = 9.8%). Conclusions: Our findings reveal Dipterans from milking environment carrying ExPEC virulence-encoding genes also identified in clinical bovine E. coli-induced infections.
Keywords: clinical mammary infections; environmental bovine mastitis; ExPEC virulence factors; fly microbiota; Matrix-Assisted Laser Desorption Ionization Time-Of- Light